Examination of ADRB2 gene expression and influence of Dexmedetomidine and Propofol on Hemodynamics after Abdominal Surgery : Dexmedetomidine and Propofol on Hemodynamics - Lin, Zongqin; Bu, Herong; Huang, Xiaomei (Cellular and Molecular Biology, 2023)
This study aimed to investigate ADRB2 gene expression and further understand the effects of dexmedetomidine on cardiac output and oxygen metabolism in tissues and organs by comparing the changes in hemodynamics after the patient has been sedated with dexmedetomidine and propofol after abdominal surgery. A total of 84 patients were randomly divided into the Dexmedetomidine Group (DEX Group with 40 cases) and Propofol Group (PRO Group with 44 cases). For the DEX Group, dexmedetomidine was used for sedation (loading dose: 1 ug/kg, infused for 10min; maintenance dose: 0.3ug/kg/h ); for the PRO Group, propofol was used for sedation (loading dose: 0.5mg/kg, infused for 10min; maintenance dose: 0.5mg/kg/h ), and the dosage of sedation drug was according to the sedation target (BIS value 60-80). Before the sedation and 5min, 10min, 30min, 1h, 2h, 4h and 6h after the loading dose, the Mindray and Vigileo monitors were used to record the BIS values and hemodynamics indices of the patients in both groups. Both DEX and PRO groups could reach the target BIS value (P> 0.05). The CI decreases before and after the administration in both groups were significant (P <0.01). The SV level of DEX group after administration was higher than before administration, while the SV level of the PRO Group after administration was lower than before administration (P <0.01). The lactate clearance rate (6h) of DEX Group was higher than that of PRO Group (P <0.05). The incidence of postoperative delirium in the Dexmedetomidine Group was lower than in the Propofol Group (P <0.05). Compared with propofol, dexmedetomidine for sedation can reduce the heart rate and increase the cardiac stroke output. Cell analysis of the ADRB2 gene showed that this gene is more expressed in the cytosol. Also, its expression in the respiratory system is more than in other organs. Considering that this gene plays a role in stimulating the sympathetic nervous system and the cardiovascular system, it can be used in the safety regulation of clinical prognosis and treatment resistance along with Dexmedetomidine and Propofol.